Inovasi Sistem Pembelajaran Masa Pandemi COVID-19 Pada Pendidikan Anak Usia Dini Di RA Hibah - Nazila Adistiarachma; Purwati Purwati (UIN Sultan Maulana Hasanudin Banten, 2022)
The global covid-19 pandemic has had far-reaching effects on education as well. Whole education, including early childhood education, makes it impossible to engage in face-to-face teaching, so an innovation of learning systems is needed to hold it. Contrary to current circumstances, some schools already carry out face-to-face learning but with strict health protocols. So RA Hibah has carried out face-to-face study with health protocol. Thus, the study is carried out with a view to discovering the innovation of the different learning systems that RA Hibah made during the pandemic, since the pandemic is not over and so the study is carried out according to conditions. Research methods use qualitative research methods, with data collection techniques of observation, interviews, and literature studies. Observations and interviews have found that innovation in learning systems during pandemics in RA Hibah, which is online learning, rolling learning, and offline learning.